Monocyte-Derived Dendritic Cell Differentiation in Inflammatory Arthritis Is Regulated by the JAK/STAT Axis via NADPH Oxidase Regulation - Marzaioli, Viviana; Canavan, Mary; Floudas, Achilleas; Wade, Siobhan C.; Low, Candice; Veale, Douglas J.; Fearon, Ursula (Frontiers in Immunology, 2020)
Monocyte-derived Dendritic cells (Mo-DC) are a distinct DC subset, involved in inflammation and infection, they originate from monocytes upon stimulation in the circulation and their activation and function may vary in autoimmune diseases. In this study we investigate the differences in Mo-DC differentiation and function in patients with Rheumatoid (RA) compared to Psoriatic arthritis (PsA). A significant increase in the Mo-DC differentiation marker CD209, paralleled by a corresponding decrease in the monocytic marker CD14, was demonstrated in RA compared to PsA, as early as one day post Mo-DC differentiation. RA monocytes ex-vivo were phenotypically different to PsA, displaying a more mature phenotype associated with altered cellular-morphology, early dendrite formation, and a significant increase in the CD40 marker. In addition, SPICE algorithm flow cytometric analysis showed distinct differences in chemokine receptors distribution in HC compared to PsA and RA CD14+ cells in the blood, with increased expression of the chemokine receptors CCR7 and CXCR4 observed in PsA and RA. In addition CD14+ cells at the site of inflammation showed a different chemokine receptor pattern between PsA and RA patients, with higher expression of CXCR3 and CXCR5 in RA when compared to PsA. The early priming observed in RA resulted in monocyte-endocytosis and antigen-uptake mechanisms to be impaired, effects that were not observed in PsA where phagocytosis capacity remained highly functional. Tofacitinib inhibited early Mo-DC differentiation, decreasing both CD209 and CD40 activation markers in RA. Inhibition of Mo-DC differentiation in response to Tofacitinib was mediated via an imbalance in the activation of NADPH-oxidases NOX5 and NOX2. This effect was reversed by NOX5 inhibition, but not NOX2, resulting in suppression of NOX5-dependent ROS production. In conclusion, RA monocytes are already primed ex vivo to become DC, evident by increased expression of activation markers, morphological appearance and impaired endocytosis capacity. Furthermore, we demonstrated for the first time that NOX5 mediates Mo-DC differentiation and function in response to Tofacitinib, which may alter DC functions.